Pengaruh Tampilan Fisik dan Lingkungan Sosial Terhadap Minat Beli dengan Gaya Hidup Konsumen Sebagai Moderator: Studi Kasus pada Perumahan Cluster di Kabupaten Indramayu - Hafizharauf Anwari Muhamad; Aang Curatman; Yusuf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The growing demand for modern housing and the shifting preferences of younger generations in Indramayu Regency have made it increasingly important to understand the factors that shape consumers’ purchase intentions. This study examines the effects of property physical appearance, social environment, and lifestyle on purchase intention. A quantitative method was employed by distributing questionnaires to prospective buyers and residents in three housing clusters: Pesona Estate, Pesona Citra Residence 2, and Graha Sudirman Cluster Alamanda. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to assess validity, reliability, direct effects, and moderating effects. The findings indicate that the physical appearance of the property has a positive and significant effect on purchase intention, highlighting building aesthetics, construction quality, and modern design as crucial factors in shaping consumer perceptions. The social environment also shows a positive and significant influence through perceptions of safety, comfort, accessibility, and social cohesion. However, lifestyle is found to exert a negative moderating effect on the relationship between both physical appearance and social environment with purchase intention, suggesting differences in visual and social preferences among Millennial and Gen Z consumers. An R2 value of 0,962 demonstrates that the three variables collectively explain 96,2% of the variance in purchase intention. These findings emphasize the importance of housing development strategies that integrate high quality physical design, stronger social interaction, and targeted lifestyle segmentation to enhance consumer appeal and purchasing decisions.